PEMANFAATAN EKSTRAK DAUN SELEDRI (Apium Graveolens) SEBAGAI ANTIKOAGULAN PENGGANTI EDTA (Ethylene Diamine Tetraacetic Acid) PADA PEMERIKSAAN JUMLAH TROMBOSIT - Ika Nurfajri Mentari; Desyani Ariza; Idham Halid (Jurnal Penelitian dan Kajian Ilmiah Kesehatan Politeknik Medica Farma Husada Mataram, 2020)
Celery (Apium Graveolens) has the same content as EDTA, namely flavonoids which can be used as anticoagulants, these flavonoids play a role in inhibiting the platelet aggregation process so that researchers want to do a research about of celery leaf extract (Apium Graveolens) as a substitute for EDTA (Ethylene Diamine Tetraacetic Acid) anticoagulants. Acid) on the examination of the platelet count. This research method is a laboratory experiment, namely the manufacture of celery leaf extract (Apium Graveolens) and homogenized with blood, which is then examined the number of platelets with 4 treatments. The examination of the platelet count also used the anticoagulant EDTA as a comparison. The results of examining the number of platelets using celery leaf extract with a concentration of 50% and using EDTA anticoagulants have the same results, so it can be stated that celery leaf extract can be used as an alternative anticoagulant as a substitute for EDTA (Ethylene Diamine Tetraacetic Acid) anticoagulant.